Development And Ex-Vivo Evaluation of Turpentine Oil Augmented Diacerein Nano-Emulgel (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Conventional topical formulations of Diacerein are often limited by poor skin permeation, drug release, and low patient compliance. Aim: This study aimed to develop and carry out ex-vivo evaluation of a turpentine oil augmented Diacerein nanoemulgel. Objectives: The objectives included characterization of the drug and polymer, pre-formulation and post-formulation studies, and stability assessment. Methodology: Four nanoemulgel formulations (F1–F4) were prepared by using varying concentrations of Carbopol 940 (0.25,0.37,0.5) as the gelling agent, with turpentine oil incorporated as a natural permeation enhancer; F4 was formulated without turpentine oil as a comparative control to know the diffusion characteristics. The formulations were evaluated for their Physical appearance, pH, Viscosity, Spreadability, Drug content, Entrapment efficiency, and Ex-vivo permeation using a modified diffusion cell, followed by accelerated stability studies. Result and discussion: All formulations were pale yellow, translucent, and homogeneous. Formulation F2 demonstrated the highest drug content (99.63 ± 0.38%), highest entrapment efficiency (82 ± 4.16%), and the most favourable balance of sustained and optimal cumulative drug release (88.44% at 5 hours), outperforming the turpentine-oil-free F4. Accelerated stability studies over 90 days confirmed that F2 retained its physicochemical integrity within acceptable limits before and after the study. Based on these findings, F2 was identified as the optimized formulation, combining efficient drug entrapment with sustained, enhanced permeation attributable to turpentine oil. Conclusion: The study concludes that the turpentine oil augmented Diacerein nanoemulgel (F2) is a promising, stable, and effective topical drug delivery system, warranting further in-vivo evaluation to confirm the therapeutic efficacy and improve the patient compliance.
Keywords: Diacerein; Nanoemulgel; Turpentine oil; Carbopol 940; Ex-vivo permeation